Perancangan Modifikasi Electric Hand Truck dengan Timing Belt untuk Jalan Bertangga - Afiff, Jamal Muhammad; Sukarnoto, Tono; Siebert, Nico (JMPM (Jurnal Material dan Proses Manufaktur), 2023)
In today's industrial needs, the most common material handling equipment in daily uses is hand truck, because of the price itself is quite cheap, flexible, and easy to operate. However, one of the weaknesses of the hand truck is it can’t through places that have different heights such as stairs. To overcome this problem, the hand truck will be modified using a timing belt which make it possible the hand truck to pass through stairs. The design modification begins with collecting the main hand truck data, followed by making several design concepts, selecting the suitable design modification concept to overcome the staircase problem and finally analyzing and calculating the components used. Design modifications are illustrated in 3D shape using Solidworks software. The result of the modified design is an electric hand truck with a timing belt with dimensions of (1037 x 455 x 1102) mm for stair-climbing with a maximum angle of stair slope equal to 30 degrees which is able to lift a load of 100 kg at a speed of 0.8 m/s.